The ranking of retail companies trading in ISE - (:unkn) unknown (My University, 2012)
The hundred percent increase in the Turkish retail sector in the last five years has continued to increase the importance of the sector in the Turkish economy, while leading to an increase also in the importance of the analysis and evaluation of the financial performance of companies by complicating the conditions of competition. This study aims to test whether or not the ELECTRE-III method is successful in determining the company with the highest performance in the sector by ranking the companies in the Istanbul Stock Exchange (ISE) - Retail Sector. The ELECTRE-III method was chosen on the grounds that it successfully guides the decision-making process and facilitates detection by eliminating the problems concerning decisionmaking in situations that offer a great number of alternatives with different features. The financial statements of the companies, which were active in the ISE Retail Sector between the years 2008 and 2010, arranged in accordance with the International Financial Reporting Standards (IFRS) were used in the research. © EuroJournals Publishing, Inc. 2012.
Keywords: Performance Analysis; Retail Sector; The ELECTRE-III Method